Super Small Polymeric Carbon Nitride Nanospheres with Core‐Shell Structure for Photocatalysis. Issue 32 (17th November 2017) - Zhang, Shengbo; Li, Mei; Qiu, Wenjun; Wei, Yan; Zhang, Gefei; Han, Jinyu; Wang, Hua; Liu, Xiao
Abstract: Novel uniform super small carbon nitride nanospheres with core‐shell structure were prepared in a one step procedure by using SiO2 hollow nanospheres as hard templates. The as‐prepared carbon nitride nanospheres with the average size of 20 nm displayed enhanced activities and durability in photocatalytic hydrogen production and the degradation of methyl orange (MO), compared to the conventional carbon nitride with bulky morphology under visible light (λ > 420 nm) irradiation. The enhancement is attributed to the nano‐scaled carbon nitride spheres with unique core‐shell structures and large surface areas, which facilitate the photogenerated charge separation and fast transport. Abstract : Novel super small carbon nitride nanospheres with core‐shell struture were prepared in a one step procedure by using SiO2 hollow nanospheres as hard templates. The as‐prepared carbon nitride nanospheres displayed enhanced activities and durability in photocatalytic hydrogen production and the degradation of methyl orange.